Combined video-assisted thoracoscopy surgery and posterior midline incision for en bloc resection of non-small-cell lung cancer invading the spine. (30th July 2021) - Hireche, Kheira; Moqaddam, Mathieu; Lonjon, Nicolas; Marty-Ané, Charles; Solovei, Laurence; Ozdemir, Baris Ata; Canaud, Ludovic; Alric, Pierre
Abstract: : OBJECTIVES: This article aims to evaluate the feasibility and safety of a hybrid video-assisted thoracic surgery (VATS) approach to achieve en bloc lobectomy and spinal resection for non-small-cell lung cancer (NSCLC). METHODS: Between October 2015 and November 2020, 10 patients underwent VATS anatomical lobectomy and en bloc chest wall and spinal resection through a limited posterior midline incision as a single operation for T4 (vertebral involvement) lung cancer. Nine patients had Pancoast syndrome without vascular involvement and 1 patient had NSCLC of the right lower lobe with invasion of T9 and T10. RESULTS: There were 5 men and 5 women. The mean age was 61 years (range: 47–74 years). Induction treatment was administered to 9 patients (90%). The average operative time was 315.5 min (range: 250–375 min). The average blood loss was 665 ml (range: 100–2500 ml). Spinal resection was hemivertebrectomy in 6 patients and wedge corpectomy in 4 patients. Complete resection (R0) was achieved in all patients. The average hospitalization stay was 14 days (range: 6–50 days). There was no in-hospital mortality. The mean follow-up was 32.3 months (range: 6–66 months). Six patients (60%) are alive without recurrence. CONCLUSIONS: VATS is feasible and safe to achieve en bloc resection of NSCLC inviding the spine without compromising oncological efficacy. Further experience and longer follow-up are needed to determine if this approach provides any advantages over thoracotomy. Abstract : Given anatomical proximity, pulmonary sulcus non-small-cell lung cancer (NSCLC) and costovertebral gutter tumours are prone to spinal invasion.